Evaluasi Aktivitas Komunikasi Pemasaran PT. Multi Flashindo Karisma dalam Meningkatkan Penjualan Produk Peralatan Dapur Komersial (Studi Kasus pada PT. Multi Flashindo Karisma Periode Tahun 2017 - 2019): Evaluasi Aktivitas Komunikasi Pemasaran PT. Multi Flashindo Karisma dalam Meningkatkan Penjualan Produk Peralatan Dapur Komersial (Studi Kasus pada PT. Multi Flashindo Karisma Periode Tahun 2017 - 2019) - Iqbal Lesmana; Riki Arswendi (Program Studi Komunikasi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Mulawarman, 2022)
The purpose of this study is to describe the evaluation of marketing communication activities carried out by PT Multi Flashindo Karisma in increasing sales of commercial kitchen equipment products for the 2017-2019 period. This research method uses a qualitative approach with the type of case study research. This research was carried out at PT Multi Flashindo in the 2017-2019 case period. The growing popularity of the Foodservice business creates new opportunities for equipment distributors in this field, including PT MFK. It is marked by the entry of various foreign restaurants that continue to arrive in Indonesia by having innovative and attractive presentations and being dominated by convinence stores, restaurants, cafes and catering businesses. many opportunities and emerging competitors offer a set of business needs. Based on the results of the discussion, it can be concluded that PT Multi Flashindo Karisma regarding the marketing evaluation of PT Multi Flashindo Karisma in increasing sales has decreased sales turnover from year to year. The marketing communication strategy carried out by PT MFK in 2017-2019 consisted of 1) first, holding an Exhibition Event consisting of Sial International Food (Sial Interfood), 2) second, namely giving special prices during the Year end sale, Ramadhan sale and Merdeka sale. and holding internal and external events consisting of cooking demos, cooking seminars, technical cooking training. However, based on the marketing strategy that has been carried out by PT MFK in 2017-2019, it still has not been able to achieve the sales target. Therefore, it can be categorized that PT MFK in the last three years has experienced a decline in sales turnover due to the company's event management being not optimal and the company's poor implementation of communication strategies in maintaining relationships with large clients.